Molecular and Metabolic Mechanism of Low-Intensity Pulsed Ultrasound Improving Muscle Atrophy in Hindlimb Unloading Rats - Lijun Sun (MDPI AG, 2021)
Low-intensity pulsed ultrasound (LIPUS) has been proved to promote the proliferation of myoblast C2C12. However, whether LIPUS can effectively prevent muscle atrophy has not been clarified, and if so, what is the possible mechanism. The aim of this study is to evaluate the effects of LIPUS on muscle atrophy in hindlimb unloading rats, and explore the mechanisms. The rats were randomly divided into four groups: normal control group (NC), hindlimb unloading group (UL), hindlimb unloading plus 30 mW/cm2 LIPUS irradiation group (UL + 30 mW/cm2), hindlimb unloading plus 80 mW/cm2 LIPUS irradiation group (UL + 80 mW/cm2). The tails of rats in hindlimb unloading group were suspended for 28 days. The rats in the LIPUS treated group were simultaneously irradiated with LIPUS on gastrocnemius muscle in both lower legs at the sound intensity of 30 mW/cm2 or 80 mW/cm2 for 20 min/d for 28 days. C2C12 cells were exposed to LIPUS at 30 or 80 mW/cm2 for 5 days. The results showed that LIPUS significantly promoted the proliferation and differentiation of myoblast C2C12, and prevented the decrease of cross-sectional area of muscle fiber and gastrocnemius mass in hindlimb unloading rats. LIPUS also significantly down regulated the expression of MSTN and its receptors ActRIIB, and up-regulated the expression of Akt and mTOR in gastrocnemius muscle of hindlimb unloading rats. In addition, three metabolic pathways (phenylalanine, tyrosine and tryptophan biosynthesis; alanine, aspartate and glutamate metabolism; glycine, serine and threonine metabolism) were selected as important metabolic pathways for hindlimb unloading effect. However, LIPUS promoted the stability of alanine, aspartate and glutamate metabolism pathway. These results suggest that the key mechanism of LIPUS in preventing muscle atrophy induced by hindlimb unloading may be related to promoting protein synthesis through MSTN/Akt/mTOR signaling pathway and stabilizing alanine, aspartate and glutamate metabolism.